3D Printing of Bone Substitutes Based on Vat Photopolymerization Processes: A Systematic Review. (8th April 2023) - Enbergs, Simon; Spinnen, Jacob; Dehne, Tilo; Sittinger, Michael
Abstract : Treatment options for critically sized bone defects are currently limited to metal osteosynthesis, autologous bone grafting, or calcium-based implants to bridge the gap. Additive manufacturing techniques pose a possible alternative. The light-basedthree-dimensional printing process of vat photopolymerization (VP) is of particular interest since it enables the printing of complex scaffold architectures at high resolution. This review compares multiple vat photopolymerization processes as well as the employed resin components' interactions with musculoskeletal cells and tissue. The results show an outstanding printing capability, exceeding the potential of other printing methods. However, despite the availability of various biocompatible materials, neither the mechanical strength of bone nor the scale necessary for clinical application has been achieved so far when relying on single material constructs. One possible solution is the development of adaptive hybrid constructs produced with multimaterial VP.